The effect of cardiac rehabilitation on anxiety and depression in percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) patients - Demir Gündoğmuş, Pınar; Gündoğmuş, İbrahim (Journal of Surgery and Medicine, 2021)
Background/Aim: It is well-known that Cardiac Rehabilitation (CR) brings about a marked improvement in depression and anxiety. As far as we know, there are no studies that research the effect of CR, Percutaneous Coronary Intervention (PCI), and Coronary Artery Bypass Grafting (CABG) on anxiety and depression. This study aimed to investigate the effects of the CR program on anxiety and depression and the change of anxiety and depression symptoms in patients who underwent PCI and CABG. Methods: This cross-sectional study included 27 patients with PCI and 16 patients who had undergone CABG admitted to the CR program. The Beck Depression Inventory (BDI) was used to determine the severity of depression symptoms, and the Situational and Trait Anxiety Inventory (STAI I-II) were used. Results: After CR, the BDI, STAI-1, and STAI-2 significantly decreased in both the PCI (P<0.001, P=0.002, and P=0.006, respectively) and CABG groups (P<0.001, P=0.001, and P=0.015, respectively) compared to before CR. The change in BDI was higher in the CABG group (P=0.033), while there were no significant differences between the changes in STAI-1 and STAI-2 scores (P=0.378 and P=0.361). Conclusion: The results of this study demonstrate the CR benefits for depression and anxiety in patients undergoing CABG and PCI. On the other hand, CABG patients show relatively more benefit in terms of depressive symptoms. Prospective and controlled studies with larger sample sizes are needed to support our findings.